2015
DOI: 10.1073/pnas.1507829112
|View full text |Cite
|
Sign up to set email alerts
|

A meningococcal vaccine antigen engineered to increase thermal stability and stabilize protective epitopes

Abstract: Factor H binding protein (FHbp) is part of two vaccines recently licensed for prevention of sepsis and meningitis caused by serogroup B meningococci. FHbp is classified in three phylogenic variant groups that have limited antigenic cross-reactivity, and FHbp variants in one of the groups have low thermal stability. In the present study, we replaced two amino acid residues, R130 and D133, in a stable FHbp variant with their counterparts (L and G) from a less stable variant. The single and double mutants decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…The two substitutions in FHbp ID 22 that increased the thermal stability in our previous study also decreased binding of human FH by 7-fold compared with the wild-type FHbp (22). Since previous studies of FHbp mutants suggested that at least 30-to 100-fold decreases in FH binding were needed to achieve optimal immunogenicity in the presence of human FH (17,18), in the present study, we sought additional FHbp substitutions to decrease FH binding further.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…The two substitutions in FHbp ID 22 that increased the thermal stability in our previous study also decreased binding of human FH by 7-fold compared with the wild-type FHbp (22). Since previous studies of FHbp mutants suggested that at least 30-to 100-fold decreases in FH binding were needed to achieve optimal immunogenicity in the presence of human FH (17,18), in the present study, we sought additional FHbp substitutions to decrease FH binding further.…”
Section: Resultsmentioning
confidence: 83%
“…As described in the introduction, we previously engineered a double mutant, L130R G133D, of FHbp ID 22 in variant group 2 that had 21°C higher thermal stability of the N-terminal structural domain (22). In the present study, to evaluate whether the mutations that increased the thermal stability of FHbp also affected its immunogenicity in the absence of binding of human FH, we immunized groups of wild-type CD-1 mice with two doses of the recombinant FHbp ID 22 wild-type or double-mutant protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations